2011
DOI: 10.1007/s10529-011-0728-z
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces ghanaensis pleiotropic regulatory gene wblA gh influences morphogenesis and moenomycin production

Abstract: The wblA(gh) gene, encoding a homologue of the WhiB-family of proteins, was identified in the sequenced genome of moenomycin producer Streptomyces ghanaensis. Deletion of the gene blocked aerial mycelium sporulation and caused a 230% increase in moenomycins production. S. ghanaensis overexpressing SSFG-01620: a homologue of extracellular protease inhibitor SCO0762, whose expression in Streptomyces coelicolor is down-regulated by wblA: showed deficiencies in sporulation similar to that of wblA(gh) knockout stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Previous reports have shown that WblA and its orthologues act as negative regulators for antibiotic biosynthesis in various Streptomyces species and that wblA deletion mutants lead to overproduction of the corresponding antibiotics (21)(22)(23)(24). In order to identify the function of wblA ch in natamycin biosynthesis in S. chattanoogensis L10, a wblA ch deletion mutant was constructed via homologous recombination, as described Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that WblA and its orthologues act as negative regulators for antibiotic biosynthesis in various Streptomyces species and that wblA deletion mutants lead to overproduction of the corresponding antibiotics (21)(22)(23)(24). In order to identify the function of wblA ch in natamycin biosynthesis in S. chattanoogensis L10, a wblA ch deletion mutant was constructed via homologous recombination, as described Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…WblA and its orthologues have been described as crucial antibiotic downregulators for the biosynthesis of various antibiotics such as actinorhodin (21), doxorubicin (22), tautomycetin (23), and moenomycin (24). Moreover, it was discovered that wblA is negatively regulated by the pleiotropic regulator AdpA in S. coelicolor (25).…”
mentioning
confidence: 99%
“…In fact, orthologs of SCO3579 (wblA) have been used for strain improvement for Streptomyces ghanaensis and Streptomyces peucetius (70,71). The additive effects of different modulators of antibiotic production have been applied in engineering optimized hosts for heterologous expression of antibiotic pathway gene sets (72).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of wblA dramatically increased antibiotic production in S. coelicolor (195), Streptomyces peucetius (196), and Streptomyces sp. strain C4412 (197), prevented nearly all aerial hyphae from sporulating in S. coelicolor (195) and Streptomyces ghanaensis (198), affected the expression of hundreds of genes in S. coelicolor (195), and slightly increased S. coelicolor oxidative stress responses (199). On the other hand, a high copy number of wblA depressed the production of ACT, RED, and CDA in S. coelicolor (and of doxorubicin in S. peucetius) (200).…”
Section: How Does Bldd Regulate Development and Antibiotic Production?mentioning
confidence: 99%